Effect of Cr/Mo carbides on corrosion behaviour of Fe_Mn_C twinning induced plasticity steel. (1st May 2020) - Wan, Hongxia; Cai, Yong; Song, Dongdong; Chen, Changfeng
Highlights: Three kinds of TWIP with different carbide contents were obtained by aging treatment. The precipitation phase of carbide is mainly MoC and Cr3 C2 . Cr/ Mo carbides and austenite matrix exist potential difference to form local galvanic couple. Abstract: Fe-Mn-C twinning-induced-plastic (TWIP) steel was prepared by adding Cr and Mo, and the effect of Cr/ Mo carbides on the corrosion behaviour of TWIP steel was studied. Different contents of carbide were obtained by aging treatment. The parameters for heat treatment method were 1150 ℃ and 2 h solid solution treatment, aging at temperature 700 °C, heat preservation for 6 and 24 h. Results show that the carbide precipitation phase occurred preferentially in the grain boundary and partly at the interior of grain when the aging time increased. The carbide precipitation phases were primarily MoC and Cr3 C2 . Cr/ Mo carbide and austenite matrices exhibited phase potential difference and formed a local galvanic couple. More carbides were precipitated, and more galvanic couples were generated as the aging time increased, which resulted in serious corrosion.